Public Sector Disinvestment in India: Price Reactions and Underpricing Issues. (May 2014) - Sehgal, Sanjay; Kumar, Muneesh; Gupta, Priyanshi
This study examines the stock market performance of Indian state-owned public sector units (PSUs), which were privatized through initial public offerings (IPOs) and further public offerings (FPOs). The analysis of stock price reaction is conducted for different event dates related to these offerings, that is, public notice date (PND), issue announcement date (IAD), price band/actual issue date (PAD), and the offer price date (OFD). The study also compares the price reaction for IPO and FPO issues. Furthermore, as the public sector equity offerings are generally sold at a discount, we also empirically analyze the degree of underpricing of such offerings. The study uses event methodology for 18 PSUs that made FPOs between 2002 and early 2013. The results report positive abnormal returns (ARs) (i.e., excess returns over and above the expected returns) after the primary offerings (IPO) of the equity. Furthermore, it was observed that in the case of first-stage further offerings (FPO-1), positive ARs are observed prior to the public notification of such offering followed by negative price reaction until the date declaration of offer price. For second-stage further public offerings (FPO-2), negative ARs (i.e., when actual returns are less than expected returns) after the public notification continue even after the date of stock offering. The price discounts on PSU issues exhibit a declining trend from IPO to successive stages of FPOs. Based on the empirical analysis, we recommend that the disinvestment should be spread over three stages of offerings, that is, primary issue (IPO), first-stage further offerings (FPO-1), and second-stage further offerings (FPO-2). In addition, selection of investment bankers and market timing needs special consideration. Furthermore, the regulatory surveillance needs to be strengthened to check the presence of ARs even before the event dates.